Strengths of fertilizer and litter effects on seedling recruitment and growth of grassland species differ depending on functional groups and seed size - Sarah Martin; Christiane Roscher (Ecology and Evolution)
Abstract Agricultural grasslands play an important role in conserving the biodiversity of the European cultural landscape. Both, litter cover and soil nutrient availability, change with grassland management, but it is not well‐studied how seedling recruitment and growth of multiple grassland species are influenced by their single or combined effects. Therefore, we studied the effects of nitrogen fertilization (100 kg N per year and ha) and litter cover (250 gdw per m2) on seedling recruitment and growth of 75 temperate grassland species (16 graminoid species, 51 forb species, 8 legume species) in a full factorial microcosm experiment. Overall, fertilizer reduced seedling emergence, while litter cover increased it even when combined with fertilization. Fertilization increased seedling height and biomass, and the combination of fertilizer and litter resulted in even stronger responses. Litter cover alone did not influence seedling biomass or seedling height. While the overall direction of treatment effects was similar across functional groups, their strengths were mostly weaker in graminoids than in non‐legume forbs and legumes. Positive litter effects on seedling emergence were stronger in large‐seeded species. Positive fertilization effects on seedling growth were stronger in small‐seeded species, while their seedling biomass was negatively affected by litter cover. In summary, our results show for multiple grassland species that the combination of litter cover and fertilization modulates their single effects. The varying sensitivity of how grassland species representing different functional groups and seed sizes respond with their seedling emergence and growth to litter cover and nitrogen fertilization indicates that the consequences of land‐use change on grassland diversity and composition already start to manifest in the earliest stages of the plant life cycle.